2020
DOI: 10.1175/mwr-d-19-0407.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Empirical Relationships between Tornado Intensity and Both Topography and Land Cover Using Rapid-Scan Radar Observations and a GIS

Abstract: This study presents an investigation into relationships among topographic elevation, surface land cover, and tornado intensity using rapid-scan, mobile Doppler radar observations of four tornadoes from the U.S. Central Plains. High spatiotemporal resolution observations of tornadic vortex signatures from the radar’s lowest elevation angle data (in most cases ranging from ~100-350 m above ground level) are coupled with digital elevation model (DEM) and 2011 National Land Cover Database (NLCD) data using a Geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…While most tornados in this region have a general southwest to northeast direction (Thom 1963), aspect was also not an important factor in predicting tree damage. Other studies have noted variability between these factors and storm intensity based on location and storm characteristics (Frazier et al 2019;Houser et al 2020). It is possible that the slope/aspect relationship deserves more focused attention in localized risk assessments, and a broad regional approach such as our study may be insu cient for elucidating a clear relationship between those variables and damage risk.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…While most tornados in this region have a general southwest to northeast direction (Thom 1963), aspect was also not an important factor in predicting tree damage. Other studies have noted variability between these factors and storm intensity based on location and storm characteristics (Frazier et al 2019;Houser et al 2020). It is possible that the slope/aspect relationship deserves more focused attention in localized risk assessments, and a broad regional approach such as our study may be insu cient for elucidating a clear relationship between those variables and damage risk.…”
Section: Discussionmentioning
confidence: 79%
“…Surface topography affects tornado direction and intensity, with even small changes in uencing near-surface in ow, structure, and path (Lewellen 2012). Steeper slopes have been shown to increase probability of tornado occurrence, likely due to the role of slope in the creation of updraft, although the relationship between elevation and tornadic activity can vary by region and storm characteristics (Frazier et al 2019;Houser et al 2020). Remote sensing studies after tornado damage in Georgia and Tennessee forests found more severe damage as tornados descended ridges and diminished damage on the ascent, and this pattern was more pronounced on shallower than steeper slopes (Cannon et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to gradients in atmospheric properties, supercells have also been found to be influenced by variability in land surface characteristics, particularly terrain [14][15][16][17]. Some studies have also noted that tornado development in supercells may be impacted by elevation changes [18][19][20][21][22] while others have explored the link between tornado formation and variations in surface roughness [22][23][24]. Numerical simulations have also shown that the development of near-ground rotation is sensitive to surface friction magnitude [25][26][27].…”
Section: Introductionmentioning
confidence: 99%